Implementasi Konsep â€œFantasia Theatreâ€ Pada Perancangan Interior Gedung Teater Musikal di Surabaya - Christabel, Valerie; Thamrin, Diana; Rakhmawati, Anik (Intra, 2018)
This theatre design is made due to the absence of proper musical theatre building in Surabaya. Musical theatre buildings require a special stage design that is flexible and can accommodate the rapid scene changes and various themes of the show. This theatre is made to not only accommodate musical theatre performances and activities but also provide a learning facility for the musical theatre communities. . In addition, the purpose of design is related to community recognition and education. This musical theatre design uses 6 steps Design Thinking approach which consists of understand, observe, point of view, ideate, prototype, and test. â€œFantasia Theatreâ€ is chosen as a concept for this theatre. The result of this design is a stage built with scenic design approach. Facilities available in the building include a lobby, box office, gallery, community space, merchandising area, auditorium and a holistic backstage area. This musical theatre design can be a solution as well as a center for concerts and musical theatre performances in Surabaya.